Detection of aflatoxins in pomegranate arils infected by Aspergillus species - C. UMAMAHESWARI1, P. NALLATHAMBI* and (Indian Phytopathology, 2009)
The market survey in Bikaner area of Rajasthan revealed that about 10-26 per cent of the total consignments of pomegranate fruits were damaged by different factors. Out of 57 per cent of the fungal colonization in total samples of damaged fruits, 21.4 per cent samples were colonized by species of Apergillus. Three pathogenic isolates of A. parasiticus (Ap-1, Ap-2 and Ap-3) and one isolate of A. flavus (Af-1) synthesized a group of aflatoxins both in culture medium and infected arils of pomegranate (cv. Ganesh) in addition to some of the unknown compounds at different Rf values. Aflatoxins B1, B2, G1 and G2 were produced in synthetic medium by the actively growing cultures of isolate Ap-1. Isolate Ap-2 produced aflatoxins G1 and G2 in culture medium but only G2 in pomegranate arils. Isolate Ap-3 has produced aflatoxin B2, G1 and G2 in culture medium while in infected arils, G1 was not detected. A. flavus (Af-1) synthesized only B2 toxins both in culture medium and infected arils. Few of the unknown compounds having intensive yellow fluorescence were also detected in both the conditions. Isolates viz., Ap-2, Ap-3 and Af-1 exhibited less number of these unknown green/yellow fluorescence compounds as compared to Ap-1. Presence of aflatoxins in pomegranate arils in response to successful colonization of A. parasiticus and A. flavus is reported for the first time.